PENGARUH GAYA KEPEMIMPINAN TERHADAP SEMANGAT KERJA KARYAWAN PADA BANK MANDIRI CABANG LANGSA - Andi Tarlis (Jurnal Investasi Islam, 2017)
This study was conducted to examine the influence of leadership style on employee morale conducted at Bank Mandiri Langsa Branch with the sampling of 68 respondents ie employees of Bank Mandiri Langsa Branch. The distribution of questionnaires was conducted in July 2016 until August 2016 as the primary data which was then analyzed using simple linear regression analysis equipment. Based on the result of simple linear regression analysis found Y = 13,900 + 0,518X and constant equal to 13,900 representing employee morale variable variable when leadership style variable is zero, or meaningful if value of leadership style variable increased 1 (one) hence the variable value of employee morale will rose by 0,518. Then obtained the value of correlation coefficient (r) is 0.579 indicates the relationship between the variables are, while the value of coefficient of determination (r2) is 0.335 or influence of leadership style to employee morale is 33.5%, the remaining of 100% is 66.5% influenced by factors such as salary, motivation, incentives, and the work environment. The result of hypothesis test (t test) got significance level from leadership style variable to employee morale obtained t-count> t-table or 5,030> 1,667 and tsig <5% or 0,00 <0,05. This shows that leadership style has an effect on employee morale of Bank Mandiri Branch of Langsa.